Unsettling Ground: Rethinking Land Tenure Security in Indonesia’s Legally Plural Setting - Tuslian, Widya Naseva (The Indonesian Journal of Socio-Legal Studies, 2026)
This study examines the inconsistencies in various regulations regarding land and land management in Indonesia, which give rise to divergent interpretations and legal uncertainty—ultimately becoming a source of conflict that is not easily resolved. The study focuses on the protracted conflict among local residents living in 26 subdistricts in Surabaya who hold “Surat Ijo” certificates. The residents believe that, as certificate holders, they have the status of owners. Meanwhile, citing various laws and regulations on land governance, the Surabaya city government maintains that these certificates affirm the residents’ status as tenants of land assets owned by the Surabaya city government. Therefore, the residents are obligated to pay rent, in addition to paying land and building taxes. In principle, tenant-occupants may acquire ownership of the land by submitting a formal application for registration to the national land registration system. However, they cannot do so because the land they occupy is an asset of the Surabaya city government. In fact, if there were a takeover of city government assets, the officials responsible could be charged with corruption. This is the root of the protracted land conflict that has reached an impasse and cannot be easily resolved.